Adaptive Fuzzy-PID Controller for Liquid Flow Control in the Heating Tank System - Yahya, Sofian; Al Tahtawi, Adnan Rafi; Wijayanto, Kartono; Faizah, Bani (International Journal of Integrated Engineering, 2022)
Liquid flow control systems are often used in some industrial processes. One of the problems is the existence of disturbance that can cause the flow response to become unstable. Thus, it is necessary to re-tuning the controller when the disturbance occurs. This study aims to design and implement an Adaptive Fuzzy-PID (AF-PID) controller for the liquid flow control in the heating tank system. We develop an industrial plant prototype of a heating tank process to test the designed controller on a laboratory scale. AF-PID controller is used to controlling the flow rate when the disturbance occurs. The nominal PID controller constants will adjust by additional PID constants when there is a disturbance based on the Mamdani type fuzzy logic rule. The hardware experimental result shows that the designed controller can maintain the stability of the liquid flow when given 50% and 100% pipe leakages with maximum undershot by 3.33% and 24% respectively.